KEMAMPUAN MENULIS CERPEN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPETHINK PAIR SHARE - Supriatna Supriatna (STKIP Siliwangi, 2016)
Short story writing ability cooperative model types using Think Pair Shareclass XII SMAN 2 Ciamis. This research is motivated low ability students inwriting short stories in class XIISMAN 2 Ciamis. The limited vocabulary ofthe students is also difficult for them in expressing their ideas into written formas well as the lack of variety of learning models used by the teacher. This studyaimed to describe the ability to write a short story using cooperative learningmodel Think Pair Share class XII SMAN 2 Ciamis.This type of research isquantitative research. The methods used in processing the data of this study isdescriptive method. Total smaple of 26 students. Sampling was done byproportional random sampling, research instruments is sheets of testperformance. Data collection techniques can be done in a way; 1) observation,2) understand the curriculum, 3) developing or designing learning scenarios,4) develop an assessment rubric, 5)implement the learning according to theRPP, and 6) carry out performance teste to write short stories.The resultsshowed that the ability to write a short story by using the type cooperativemodel Think Pair Share class XII SMAN 2 Ciamis overall quite good. It wasseen on the average value of students as follows; 1) the average grade writingshort stories with the aspect of character and characterzation are 92,12;2) theaverage value of writing a short story by observing the grooves is 81; 3)average value of writing a short story by observing the background is 65,58.The average value of short story writing skills class XII SMAN 2 Ciamis, afterusing the type cooperative model Think Pair Share overall was 79,27 withqualifying well. The observations in class XII SMAN 2 Ciamis research foundadvantages and disadvantages of cooperative learning model Think PairShare. The advantages of this model are; 1) group more easily and quicklyshape it; 2) enhance creativity and active participation of students towardslearning; 3) the acceptance of greater individual. Whileshortcomings/weaknesses of this model is the number of groups that formed somany members of the group are reported and nedd to be monitored.Keywords:model types using Think Pair Share